Altered Connexin 43 and Connexin 45 protein expression in the heart as a function of social and environmental stress in the prairie vole. (January 2015) - Grippo, Angela J.; Moffitt, Julia A.; Henry, Matthew K.; Firkins, Rachel; Senkler, Jonathan; McNeal, Neal; Wardwell, Joshua; Scotti, Melissa-Ann L.; Dotson, Ashley; Schultz, Rachel
Abstract Exposure to social and environmental stressors may influence behavior as well as autonomic and cardiovascular regulation, potentially leading to depressive disorders and cardiac dysfunction including elevated sympathetic drive, reduced parasympathetic function, and ventricular arrhythmias. The cellular mechanisms that underlie these interactions are not well understood. One mechanism may involve alterations in the expression of Connexin43 (Cx43) and Connexin45 (Cx45), gap junction proteins in the heart that play an important role in ensuring efficient cell-to-cell coupling and the maintenance of cardiac rhythmicity. The present study investigated the hypothesis that long-term social isolation, combined with mild environmental stressors, would produce both depressive behaviors and altered Cx43 and Cx45 expression in the left ventricle of prairie voles – a socially monogamous rodent model. Adult, female prairie voles were exposed to either social isolation (n = 22) or control (paired, n = 23) conditions (4 weeks), alone or in combination with chronic mild stress (CMS) (1 week). Social isolation, versus paired control conditions, produced significantly (p < 0.05) increased depressive behaviors in a 5-min forced swim test, and CMS exacerbated (p < 0.05) these behaviors. Social isolation (alone) reduced (p < 0.05) total Cx43 expression in the left ventricle; whereas CMS (but not isolation) increased (p < 0.05) total Cx45 expression and reduced (p < 0.05) the Cx43/Cx45 ratio, measured via Western blot analysis. The present findings provide insight into potential cellular mechanisms underlying altered cardiac rhythmicity associated with social and environmental stress in the prairie vole.